ANALYTICAL METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF CYAMEMAZINE TARTRATE IN FORMULATION BY RP-HPLC WITH STABILITY INDICATING - KATOLKAR, PARIMAL; JAISWAL, SHREYA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
High-performance liquid chromatography (HPLC) technique for cyamemazine tartrate (CYMT) was developed and validated according to the International Conference on Harmonization (ICH) Q2 (R1) guidelines. The developed and validated method for estimating CYMT from a bulk and its pharmaceutical dosage form was found to be a simple, precise, accurate, fast, and stable reverse phase HPLC (RP-HPLC) approach. For chromatographic separation, a Hypersil BDS C18 (250 mm × 4.6 mm, particle size: 5 μm) column was employed with a mobile phase of methanol and buffer (80:20 v/v) flow rate at 1.0 ml/min at room temperature. For detection, a wavelength of 270 nm was utilized. With a run period of 10 min, the CYMT was eluted at 4.38 min. With a correlation coefficient (r2) of above 0.9996, and limits of detection and quantitation (LOD and LOQ) of 0.27 and 0.80 μg, respectively, the method exhibited a dynamic linear response across 30–90 μg/ml. The repeatability of batch injections for intra- and inter-assay precision and accuracy testing was likewise satisfactory. The stability of CYMT was studied under thermal, acid, alkali, and oxidation conditions, as well as photodegradation conditions. The stability of the approach is demonstrated by the presence of CYMT and its breakdown products. The recommended technique exhibited great linearity, accuracy, precision, robustness, LOD, LOQ, and system suitability within the acceptance limit. The study’s findings indicate that the method is rapid, simple, accurate, exact, and linearly stable, implying that an HPLC method for CYMT has been developed and validated, and that it may be used for routine quality control analysis.